1998
DOI: 10.1161/01.atv.18.5.773
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Metabolism of Postprandial Lipoproteins After a High-Monounsaturated-Fat Versus a High-Carbohydrate Diet in Patients With Type 1 Diabetes Mellitus

Abstract: Abstract-There is little information comparing the effects of a high-monounsaturated (Mono)-fat versus a highcarbohydrate (CHO) diet in patients with type 1 diabetes mellitus. In the present study, the effects of these diets on a number of metabolic parameters were compared. Seventeen normolipidemic, nonobese patients with type 1 diabetes were provided with the diets for 4 weeks each in a randomized, crossover design. The percentages of Mono fat of the two diets were 25 Mono versus 9 CHO, with a corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…This lack of correlation may be explained by the fact that our patients are in reasonably good blood glucose control (HbA1c ¼ 6.971.7). (Georgopoulos et al, 1998;Koutsari et al, 2000;Iovine et al, 2004a). Population-based studies looking at this specific aspect are very few (Sharrett et al, 2001;Van Wijk et al, 2001;Geluk et al, 2004) and none has been performed in a diabetic population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of correlation may be explained by the fact that our patients are in reasonably good blood glucose control (HbA1c ¼ 6.971.7). (Georgopoulos et al, 1998;Koutsari et al, 2000;Iovine et al, 2004a). Population-based studies looking at this specific aspect are very few (Sharrett et al, 2001;Van Wijk et al, 2001;Geluk et al, 2004) and none has been performed in a diabetic population.…”
Section: Discussionmentioning
confidence: 99%
“…Although this concordance of results is true for fasting TG concentrations, less is known about the effects of dietary CHO and fat on postprandial TG. The few data available on this topic have been obtained especially in acute experiments and remain substantially controversial, with some studies showing an increase after high CHO diets or high-fat meals and others just the opposite, that is, an increase in postprandial TG concentrations after high-fat diets or high-fat meals (Georgopoulos et al, 1998;Koutsari et al, 2000;Pieke et al, 2000;Iovine et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…A delay in CM clearance would imply a prolonged postprandial hyperlipidemia, which supposedly leads to increased deposition of CM contents into the arterial wall and to an unfavorable translocation of cholesteryl-esters from HDL to CM (13,14). Delays in CM clearance are amenable to dietary intervention, by changing the intake of fish oil (long chain PUFA) (15), monounsaturated-fat (16), or carbohydrate (17). Yet, it is not known whether CM clearance is delayed in late teenagers with DM1.…”
mentioning
confidence: 99%
“…Several studies have compared the effects on PPL of a diet high in total fat and MUFA (HFMUFA) (olive oil) vs. low in fat and high in carbohydrates (LFHC) and/or vs. a diet high in fat and SFA (HFSFA) (butter). Many (21,24,33,34,39,46,68,69,76,79,90), but not all (4,14,20,26,65,70,71,85), found that the HFMUFA diet was superior to the other two diets in several aspects of postprandial TAG metabolism in both healthy and nonhealthy volunteers (Tables 1 and 2).…”
Section: Amount and Type Of Fatmentioning
confidence: 99%
“…Advantages of a HFMUFA diet have also been found in subjects with metabolic syndrome (34) or type 2 diabetes (46,69). Of two studies performed in type 1 diabetics, the first (26) found that 4 wk on a HFMUFA diet increased PPL. However, a more recent study with a more prolonged intervention (6 mo) showed that 24-h TAG was lower after a HFMUFA than with a LFHC diet (79).…”
Section: Amount and Type Of Fatmentioning
confidence: 99%